Tourism training and education, Community empowerment and Participation in tourism planning and development. A case of Uganda - Tukamushaba, Eddy K.; Okech, Roselyne N. (Journal of Tourism, 2011)
This paper develops a model that explains the relationship between tourism training and education, community empowerment and participation in tourism planning and development in communities around protected areas in Uganda. Data was collected using a survey conducted in communities around Queen Elizabeth National Park in the western part of Uganda. The study focused of adult members in households following Uganda National Bureau of statistics guidelines of 2002 population census. A total of 310 questionnaires were distributed and 294 were utilized for data analysis. Qualitative data was also solicited through interviews with selected residents. Results indicate that tourism training and education together with community empowerment are strong predictors of community participation and involvement in tourism planning and development. Community empowerment was found to have a greater impact on the outcome variable. Conducting research into this important area of community participation and involvement tourism planning and development is expected to contribute knowledge towards the body of research in tourism growth and development in developing countries. When Communities living near the protected tourism resources are empowered to make investment decisions in tourism ventures through tourism education and training, it is likely to motivate them to get involved in planning and development of tourism. This study is one of the first in attempting to develop a model that explains the relationship between tourism education and training, community empowerment and participation and involvement in tourism planning and development in a Uganda setting.
Keywords: Tourism education and Training; community Empowerment; Tourism, Planning and development